Spatiotemporal analysis of dog-mediated rabies in Zambia: A retrospective study, 2013–2022 - Humphrey Banda; Amos Hamukale; Chitwambi Makungu; Wezi Kachinda; Masuzyo Ngoma; Liywalii Mataa; James Blazer Banda; Walter Muleya; Dabwitso Banda; Nyambe Sinyange (Journal of Interventional Epidemiology and Public Health)
Introduction: Rabies remains a significant public health threat in Zambia, particularly dog-mediated rabies. Despite national control efforts through vaccination, the disease persists, especially in rural regions with weak surveillance systems. This study aimed to analyse the spatial and temporal distribution of rabies cases in Zambia from 2013 to 2022 to identify high-risk areas and support targeted interventions. Methods: This retrospective study utilized secondary data obtained from the National Livestock Epidemiological Information Centre (NALEIC) and the Central Veterinary Research Institute (CVRI), comprising all reported canine rabies cases from January 2013 to December 2022. A purely spatial cluster analysis using the Discrete Poisson model in SaTScan v10.3 was conducted to detect rabies clusters across 10 provinces of Zambia. A Poisson regression was used to assess seasonal trends in rabies incidence. Results: A total of 225 rabies cases were reported between 2013 and 2022. The cumulative incidence rate was 23.2 cases per 100,000 dogs. A high-risk cluster was identified encompassing Central, Copperbelt, Luapula, and Lusaka provinces, with an incidence rate of 38.9 cases per 100,000 dogs and a statistically significant relative risk (RR) of 2.7 and 95% confidence interval (CI)= 2.07 – 3.53, indicating dogs in this cluster were 2.7 times more likely to be reported rabid than those outside. Two statistically significant low-risk clusters were identified: one covering North-Western, Southern, and Western province with incidence of 13.3/100,000, RR of 0.93 (95%CI= 0.71-1.22), and another in Eastern Province (incidence of 11.4/100,000, RR =0.80, 95%CI= 0.47-1.36) though their relative risks were not statistically significant. Northern and Muchinga provinces were non-statistically significant low-risk clusters. Seasonal trends showed increased rabies cases during February, March, and November, suggesting temporal peaks. Conclusions: This study underscores significant regional and seasonal variation in rabies incidence in Zambia. High-risk areas, especially those with dense dog populations and limited vaccination coverage, should be prioritized for intensified rabies control efforts, including mass vaccination and enhanced surveillance. The presence of low-risk clusters may reflect underreporting, necessitating improved community engagement and diagnostic capacity. These findings are crucial for informing Zambia’s strategy to eliminate dog-mediated human rabies by 2030.